Enhanced Sodium‐Ion Storage Performance of a 2D MoS2 Anode Material Coated on Carbon Nanotubes. Issue 5 (1st March 2021) - Li, Wanying; Bashir, Tariq; Wang, Jiaqi; Zhou, Shaowen; Yang, Shiqi; Zhao, Jianqing; Gao, Lijun
Abstract: Molybdenum disulfide (MoS2 ) is considered a promising anode material for sodium‐ion batteries (SIBs). However, it suffers from poor kinetics and rapid capacity decay. In this work, a coaxial heterostructure composed of MoS2 nanosheets coated on carbon nanotubes (CNTs) is reported, where the MoS2 layers are less stacked at the surface of the CNTs substrate with an enhanced interlayer spacing, which is prepared through a simple one‐pot hydrothermal preparation. The MoS2 @CNTs composite material is proven to have superior rate performance as an anode material for SIBs, which delivers 508, 418, 359, 305, 258, and 183 mAh/g at current densities of 0.1, 0.2, 0.5, 1, 2, and 5 A/g, respectively, together with excellent cycling stability to retain 360 mAh/g after 400 cycles at 0.5 A/g, owing to the robust combination of MoS2 and CNT components. This work offers a way to synthesize heterostructured composite materials with great performance superiority for large‐scale energy storage systems. Abstract : Power in 2D : MoS2 nanosheets are evenly coated on carbon nanotubes by using a simple one‐pot hydrothermal method. The electrochemical performance of the obtained material for sodium storage are studied.